Comparative Efficacy of Topical N-Acetylcysteine-Doxycycline versus Benzoyl Peroxide-Doxycycline in Moderate Acne Vulgaris: Add-on Double-Blind Randomized Controlled Trial - Parvizi, Mohammad Mahdi; Mosallanezhad, Parisa; Hekmat, Maryam; Alipour, Shohreh; Fazelzadeh Haghighi, Negin (Dermatology Practical & Conceptual, 2026)
Introduction: Acne vulgaris is a prevalent skin disorder affecting approximately 85% of adolescents. While topical retinoid and benzoyl peroxide (BPO) are standard treatments, their side effects often decrease patient adherence. Objectives: Due to the potential side effects of these drugs, we decided to explore the efficacy and safety of topical N-acetylcysteine (NAC) plus doxycycline compared to BPO-doxycycline in moderate acne vulgaris. Method: In this double-blind, randomized clinical trial, 40 patients were divided into two groups: Group A received 100 mg/day doxycycline+5% NAC, while Group B received 100 mg/day doxycycline +5% BPO. Patients were assessed over three months using Total Lesion Count (TLC), Investigator Global Assessment (IGA), Global Acne Grading System (GAGS), and Cardiff Acne Disability Index (CADI). Statistical analysis was performed using STATA 14.2, with p < 0.05 considered significant. Results: The NAC group showed a significantly greater reduction in CADI scores (MD=-3.60, 95% CI: -4.26 to -2.95, p < 0.001), GAGS scores (MD = -9.76, 95% CI: -11.84 to -7.68, p < 0.001), and TLC (MD = -4.29, 95% CI: -6.38 to -2.19, p = 0.002) compared to BPO. IGA scores also improved more significantly in the NAC group (MD = -0.85, 95% CI: -1.12 to -0.58, p < 0.001). Only one patient reported mild scaling with NAC, suggesting better tolerability. Conclusion: Topical NAC combined with doxycycline was significantly more effective than BPO-doxycycline in reducing acne severity and lesion count, with minimal adverse effects. NAC may serve as a more efficacious alternative for treating moderate acne vulgaris.